EKSPERIMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DENGAN MIND MAPPING DITINJAU DARI GAYA BELAJAR PADA MATERI OPERASI ALJABAR SISWA KELAS VIII SMP NEGERI DI KABUPATEN SRAGEN TAHUN PELAJARAN 2014/2015 - Primasari, Dessy Marlinda; Mardiyana, Mardiyana; Sari Saputro, Dewi Retno (Jurnal Pembelajaran Matematika, 2016)
Abstract : The aim of this research was to know the effect of learning models on mathematics achievement viewed from the student learning style. The learning models compared were PBL with Mind Mapping, PBL and Classical learning. This research  was a quasi experimental with the factorial design of 3 x 3. The population of this research was all students of class VIII of the State Junior High School in the region of Sragen Regency. The sampling technique used was stratified cluster random sampling. The size of the sample was 293 students, consisted of 98 students in experimental class 1, 98 students in experimental class 2, and 97 students in control class. The instruments of gather the data were test of achievement on the learning and questionnaire of learning style. The proposed hypotheses of the research were analyzed by using the two way analysis of variance with unbalance cells. The results of the research were as follows. (1) The PBL learning model with Mind Mapping gave the same achievement as students with PBL learning model, the PBL learning model with Mind Mapping gave better achievement than students with classical learning model, the PBL learning model gave the same achievement as students with classical learning model. (2) The students with the visual learning style had the same learning achievement as those with the auditory and kinesthetic learning style. The students with the auditory learning style had the same learning achievement as those with the kinesthetic learning style. (3) In each category of the learning style,  the PBL learning model with Mind Mapping gave the same achievement as students with PBL learning model and classical learning model, the PBL learning model gave the same achievement as students with classical learning model. (4)  In each of the learning models, the students with the visual learning style had the same learning achievement as those with the kinesthetic and auditory learning style, and the students with the kinesthetic learning style had the same learning achievement as those with the auditory learning style.Keywords : PBL, Mind Mapping, Learning Style.